Learning on the Personality Development - Saritha Mididoddi (AG Volumes, 2021)
The purpose of this research is to better understand the role that personality traits play in the workplace and how they might be used to further a variety of organisational goals. The improper sort of personality always leads disastrously and causes unnecessary tensions and anxieties to develop in workplaces. When seen from the perspectives of employee-employer connections, peer relationships, and boss-subordinate relationships, the tension and anxiety present in every firm are readily apparent. Organizational conflicts and their effects on work satisfaction are often cited as important contributing factors to a person’s unique personality. Youth personality development criteria and the causes for individual variances were the subject of this study.